Designing the Behavioral Engagement Ecosystem in Project-Based Learning - Maria Coney Garcia Pallones (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
The study examines how specific design features of Project-Based Learning (PBL) shape and sustain behavioral engagement among young learners, addressing a gap in research that has largely focused on PBL’s effectiveness rather than the factors that drive active participation, effort, and persistence. Semi-structured interviews with elementary teachers were analyzed through the lens of Self-Determination Theory (SDT), revealing three interrelated factors critical to engagement: (1) voice, choice, and ownership, which nurture autonomy; (2) clear pathways to mastery, facilitated through scaffolding and feedback, which build competence; and (3) meaningful social connections, fostered through collaboration and teacher support, which satisfy relatedness. These findings informed the development of the Triadic Model of Behavioral Engagement in PBL, positioning autonomy, competence, and relatedness as interdependent drivers of sustained behavioral engagement. Teachers reported that these factors operate synergistically, forming a motivational ecosystem in which engagement and learning outcomes reinforce each other, producing sustained effort, participation, and ownership. Challenges such as initial student confusion and the need for ongoing scaffolding highlight the importance of responsive and flexible teaching.